Pengaruh Permainan Balok Angka Terhadap Kemampuan Berhitung Anak Usia 5-6 Tahun di PAUD Marqisah - Raudah Raudah; Amilda Amilda; Fuaddilah Ali Sofyan; Leny Marlina (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2021)
This research is entitled "The Effect of Number Block Game on Counting Ability of Children 5-6 Years Old at Marqisah PAUD, Segamit Village, Semende Darat Ulu, Muara Enim". As for the problem of this research, is there any influence of the number block game on the numeracy ability of children aged 5-6 years at PAUD Marqisah, Segamit Village, Semende Darat Ulu, Muara Enim. 5-6 years in PAUD Marqisah, Segamit Village, Semende Darat Ulu, Muara Enim. This type of research is pre-experimental with one group pre-test-post-test design (one group of objects). The number of samples of children is 10 children consisting of 1 girl and 9 boys. Data collection techniques in the study used initial observation before being treated with learning using number block games, observation was used to collect data during treatment, tests in the form of scores were carried out to determine test results were given treatment and documentation in the form of photos. The data analysis technique used in this study used normality test, homogeneity test and hypothesis testing. The results of the hypothesis in this study obtained tcount = 6, 2616487343 while dk = 10 + 10-2 = 18 with a 5% significance level so that ttable = 1,734 is obtained because tcount = 6, 2616487343 > ttable = it can be concluded that Ho is rejected, meaning that there is an influence the number block game on the numeracy skills of children aged 5-6 years at PAUD Marqisah, Segamit Village, Semende Datar Ulu, Muara Enim.